Optimal control for a prototype of an active magnetic bearing system - Aragón Ayala, Danielo Eduardo (2017)
First applications of the electromagnetic suspension principle have been in experimental physics, and suggestions to use this principle for suspending transportation vehicles for high-speed trains go back to 1937. There are various ways of designing magnetic suspensions for a contact free support, the magnetic bearing is just one of them [BCK+09]. Most bearings are used in applications involving rotation. Nowadays, the use of contact bearings solves problems in the consumer products, industrial machinery, or transportation equipment (cars, trucks, bicycles, etc). Bearings allow the transmition of power from a motor to moving parts of a rotating machine [M+92]. For a variety of rotating machines, it would be advantageous to replace the mechanical bearings for magnetic bearings, which rely on magnetic elds to perform the same functions of levitation, centering, and thrust control of the rotating parts as those performed by a mechanical bearing.